Maladjustment of the psychosocial behavior of student from UNMSM - Velásquez Centeno, Carlos (1998)
The investigation objective was to set the profile of maladjustment psychosocial behavior related to mental health in 911 students from first year to senior in 23 UNMSM Academic-Professional Schools and at the same time to establish the validity and reliability in the inventory of maladjustment in psychosocial behavior. The results obtained show that the item structure of the scales of anxiety, depression, socialization, aggressiveness, resentment, distrust, mental rigidness, sexual disorders and social maladjustment, dependency, antisocial behavior and national uproot, all keep their very own structure; not so the scale items of low self-esteem and social approval, Therefore men who express antisocial and national uproot behavior are significantly higher than women in showing higher punctuations in anxiety, depression, somatization, sexual maladjustment and dependency scales than men. While comparing the INDACPS scales of each Academic-Professional School, it is only observed differences on the distrust scale in Psychology and Accounting Schools.